2012
DOI: 10.1111/j.1365-2184.2012.00836.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of culture of mesenchymal stem cells: a comparison of conventional plate and microcarrier cultures

Abstract: Compared to conventional plate culture, culture using gelatine porous microcarrier Cultispher-S was superior for large-scale production of rat MSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
1
11
0
1
Order By: Relevance
“…Bioreactor‐facilitated stem cell expansion has already been achieved using multiple systems, ranging from multilayered cell factories to microcarriers in stirred tank bioreactors (Jung et al , ). Different groups have already shown that the stem cell phenotype can be maintained in these systems, despite the external hydrodynamic stresses applied to the cells by fluid flow during culture (Hewitt et al , ; Chang et al , ; Jung et al , ). However, despite the 3D shape of the carriers used in these systems, cells predominantly grow in a monolayer, which does not reproduce the native environment of the cells (Haycock, ).…”
Section: Introductionmentioning
confidence: 99%
“…Bioreactor‐facilitated stem cell expansion has already been achieved using multiple systems, ranging from multilayered cell factories to microcarriers in stirred tank bioreactors (Jung et al , ). Different groups have already shown that the stem cell phenotype can be maintained in these systems, despite the external hydrodynamic stresses applied to the cells by fluid flow during culture (Hewitt et al , ; Chang et al , ; Jung et al , ). However, despite the 3D shape of the carriers used in these systems, cells predominantly grow in a monolayer, which does not reproduce the native environment of the cells (Haycock, ).…”
Section: Introductionmentioning
confidence: 99%
“…For MSCs, spreading shape versus round shape can change the fate of cell proliferation as well as osteogenic, adipogenic, or chondrogenic differentiation, which may be mediated through RhoA/ROCK signaling (Figure ). Despite the recent advances of MC technology for MSC cultivation, there are still significant challenges to fully exploit the potential of MCs for stem cell fate decision. There is clearly a limited understanding about how the MSCs attach to and interact with MCs.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…This culture system showed some drawbacks such as cell aggregation during expansion. To avoid cell aggregation, some studies proposed controlling operating parameters such as agitation rate, cell density, and addition of carriers . Sometimes, due to the smooth surface of microcarriers such as glass microcarriers and Cytodex, MSCs cannot attach firmly and may detach and be washed away during medium changes .…”
Section: Introductionmentioning
confidence: 99%